2020
DOI: 10.1371/journal.pone.0235604
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary bypass and internal thoracic artery: Can roller or centrifugal pumps change vascular reactivity of the graft? The IPITA study: A randomized controlled clinical trial

Abstract: Background Cardiopulmonary bypass (CPB) induces a systemic inflammatory response (SIRS) and affects the organ vascular bed. Experimentally, the lack of pulsatility alters myogenic tone of resistance arteries and increases the parietal inflammatory response. The purpose of this study was to compare the vascular reactivity of the internal thoracic arteries (ITAs) due to the inflammatory response between patients undergoing coronary artery bypass grafting (CABG) under CPB with a roller pump or with a centrifugal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…With regard to the maintenance of anesthesia, most studies found similar VOTderived NIRS values when comparing different anesthetics. In general, the RA decreased during both non-cardiac and cardiac surgery, indicating an impairment of vascular reactivity, which might be caused by a surgically induced inflammatory response [44][45][46]. During CPB, a decrease in the RA was consistently reported, reflecting an impairment in vascular reactivity possibly caused by an altered myogenic tone due to lack of pulsatile flow and increased inflammatory response [44].…”
Section: Key Findingsmentioning
confidence: 93%
See 2 more Smart Citations
“…With regard to the maintenance of anesthesia, most studies found similar VOTderived NIRS values when comparing different anesthetics. In general, the RA decreased during both non-cardiac and cardiac surgery, indicating an impairment of vascular reactivity, which might be caused by a surgically induced inflammatory response [44][45][46]. During CPB, a decrease in the RA was consistently reported, reflecting an impairment in vascular reactivity possibly caused by an altered myogenic tone due to lack of pulsatile flow and increased inflammatory response [44].…”
Section: Key Findingsmentioning
confidence: 93%
“…In general, the RA decreased during both non-cardiac and cardiac surgery, indicating an impairment of vascular reactivity, which might be caused by a surgically induced inflammatory response [44][45][46]. During CPB, a decrease in the RA was consistently reported, reflecting an impairment in vascular reactivity possibly caused by an altered myogenic tone due to lack of pulsatile flow and increased inflammatory response [44]. Consistently, after weaning from CPB and restoration of pulsatile blood flow, the RA values generally increased towards pre-CPB values.…”
Section: Key Findingsmentioning
confidence: 96%
See 1 more Smart Citation